1999
DOI: 10.1046/j.1469-0705.1999.13030161.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine management of fetal parvovirus B19 infection

Abstract: Fetal parvovirus infection can lead to marked anemia and hydrops formation. Cordocentesis allows precise assessment of fetal anemia which can then be corrected by intravenous transfusion. Under this regimen, the outcome proved favorable in the majority of fetuses, even those that were severely anemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 0 publications
5
51
0
7
Order By: Relevance
“…The chance of an adverse fetal outcome after infection seems to be greatest between 11 and 23 weeks of gestation, which correlates with the hepatic period of hematopoietic activity (366,367). Cordocentesis allows precise assessment of fetal anemia, which might then be corrected by intravenous transfusion of erythrocytes (292). Accordingly, in series of hydropic fetuses the case fatality rate may be almost 50% (102,195,317), but (ii) Congenital anemia.…”
Section: B19 Infection In Pregnancy (I) Hydrops Fetalismentioning
confidence: 99%
“…The chance of an adverse fetal outcome after infection seems to be greatest between 11 and 23 weeks of gestation, which correlates with the hepatic period of hematopoietic activity (366,367). Cordocentesis allows precise assessment of fetal anemia, which might then be corrected by intravenous transfusion of erythrocytes (292). Accordingly, in series of hydropic fetuses the case fatality rate may be almost 50% (102,195,317), but (ii) Congenital anemia.…”
Section: B19 Infection In Pregnancy (I) Hydrops Fetalismentioning
confidence: 99%
“…Retrospective studies have shown B19 infection to be responsible for 10-50% of cases of hydrops fetalis, in which the etiology was unknown . Two reports have proposed management plans for pregnant women exposed to individuals with B19 infection and for women shown to be infected upon serological testing (Levy et al 1997;Schild et al 1999). These studies, however, showed some discrepancies, and further study is necessary in order to establish clinical practice guidelines.…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%
“…Management with intrauterine transfusion (IUT) can correct fetal anaemia and may reduce the mortality of fetal Parvovirus B19 infection significantly. Fetal mortality rate due to Parvovirus B19-induced hydrops has been reported as high as 30% without IUT 5,6 . Management with IUT guided by appropriate anaemia Z-scores in the absence of fetal myocarditis may reduce mortality by more than 50% 5 .…”
Section: Introductionmentioning
confidence: 99%